Analisis Kepastian Hukum Putusan Pra Peradilan Terhadap Tersangka Tindak Pidana Korupsi (Studi Putusan Pra Peradilan Nomor:02/Pid.Pra/2022/Pntbh) - Zainuddin Kasim; Fitri Wahyuni; Ali Azhar (Indragiri Law Review, 2025)
This study explores the challenges of legal certainty within pretrial institutions in Indonesia, particularly in the context of corruption. The study focuses on Pretrial Decision Number 02/Pid.Pra/2022/PN Tembilahan, which annulled Indra Muchlis Adnan's suspect status. Problems arise when investigators frequently ignore the effectiveness of the final and binding pretrial decision through re-determination of the suspect. Using a normative juridical research method with a case-based and statutory approach, the results show that legal certainty is not achieved absolutely due to ambiguity in the implementation of new evidence (novum) as stipulated in PERMA No. 4 of 2016. The study concludes that the judicial oversight function must be strengthened so that pretrial proceedings are not merely procedural formalities but rather substantive protectors of the suspect's human rights.